2006
DOI: 10.1007/s11099-006-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

High photosynthetic efficiency of a rice (Oryza sativa L.) xantha mutant

Abstract: Comparative analysis revealed that a xantha rice mutant (cv. Huangyu B) had higher ratios of chlorophyll (Chl) a/b and carotenoids/Chl, and higher photosynthetic efficiency than its wild type parent (cv. II32 B). Unexpectedly, the mutant had higher net photosynthetic rate (P N ) than II32 B. This might have resulted from its lower non-photochemical quenching (q N ) but higher maximal photochemical efficiency (F V /F M ), higher excitation energy capture efficiency of photosystem 2 (PS2) reaction centres (F V ′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…A large reduction in Chl content might not result in a corresponding reduction in photosynthesis and carbon assimilation in a couple of yellow-green maize mutants (Jenkins et al 1989). In rice leaf mutants no relation may exist between Chl content and P N (Lin et al 2003, Zhou et al 2006, which is consistent with our results. The chlorina mutant was limited in capturing photon energy by low Chl content (Table 1) and lesser chloroplast grana lamellae (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A large reduction in Chl content might not result in a corresponding reduction in photosynthesis and carbon assimilation in a couple of yellow-green maize mutants (Jenkins et al 1989). In rice leaf mutants no relation may exist between Chl content and P N (Lin et al 2003, Zhou et al 2006, which is consistent with our results. The chlorina mutant was limited in capturing photon energy by low Chl content (Table 1) and lesser chloroplast grana lamellae (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The chlorina mutant could reduce thermal dissipation and increase ETR to partially reduce deficiency of photon energy (Xu et al 2004, Zhou et al 2006. High ETR under natural irradiance was propitious to RuBP regeneration, and might enhance the activities of photosynthetic enzymes (Harbinson et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study in acrylic-based polyurethane coatings with nano-silica particles it was reported that the film strength considerably increases and elongation at break obviously decreases with increasing nano-silica content. This is likely due to the reaction of isocyanate with hydroxyl groups on the surfaces of nanosilica, which leads to a higher cross-linking degree of the film [28]. However, the crosslinked macromoleculaes have a different behaviour in the case of aliphatic polyesters, which due to their low molecular weights are very brittle materials.…”
Section: Morphological Thermal and Mechanical Properties Of Pesu/sio mentioning
confidence: 99%
“…The irradiance (I) response curves of photosynthesis of different plant species have often been reported (Terashima and Saeki 1983, Vogelmann 1989, Ögren 1993, Kyei-boahen et al 2003, Marschall and Proctor 2004, Chen and Xu 2006, Fu et al 2006, Gao et al 2006, Zhou et al 2006. Accurate assessment of photosynthetic rate is of fundamental importance for understanding the photochemical yield of the process, and it is also fundamental to understanding the relationship between I and the net rate of photosynthesis (P N ) driven by photon energy.…”
Section: --mentioning
confidence: 99%